2018
DOI: 10.1088/2058-6272/aac647
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric pressure gliding arc discharge plasma treatments for improving germination, growth and yield of wheat

Abstract: Wheat (Triticum aestivum) seeds were treated with atmospheric pressure gliding arc discharge plasmas to investigate the effects on water absorption, seed germination rate, seedling growth and yield in wheat. The surface architectures and functionalities of the seeds were found to modify due to plasma treatments. 6 min treatment was provided 95%-100% germination rate. For the treatment duration of 3 and 9 min the growth activity, dry matter accumulation, leaves chlorophyll contents, longest spikes, number of sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…However, for high NTP doses, i.e., over optimal treatment time (in this case, 30 min), all the growing properties decreased under untreated. Also in [48], the grains treated for 3 and 6 minutes had the highest germination rate 95-100%. However, the further increments of NTP treatment time caused the decrease of the germination rate.…”
Section: Seed Germination and Seedling Initial Growthmentioning
confidence: 91%
See 3 more Smart Citations
“…However, for high NTP doses, i.e., over optimal treatment time (in this case, 30 min), all the growing properties decreased under untreated. Also in [48], the grains treated for 3 and 6 minutes had the highest germination rate 95-100%. However, the further increments of NTP treatment time caused the decrease of the germination rate.…”
Section: Seed Germination and Seedling Initial Growthmentioning
confidence: 91%
“…Concerning with germination, Gidea et al [61] reported also the increase of average length of roots and sprouts and vigor index, but after exposure times over 30 min, all measured properties decreased close to or under untreated ones. In the experiments of Roy et al [48], plant lengths from grains exposed for 3 and 6 min increased to 23 cm and 22 cm, respectively, while the control was 21 cm at the same incubation period. After 20 days of sowing, the longest plant height was 23 cm for the exposed seed, while the control was 19 cm.…”
Section: Seed Germination and Seedling Initial Growthmentioning
confidence: 91%
See 2 more Smart Citations
“…Gliding sparks produced by self-stimulated acoustic waves allow for chemical conversion rate as high as 50%, having much better performance in comparison with the conventional pulsed plasmas [22]. Several authors have also successfully used GA reactors to stimulate the growth of seeds of plants, such as wheat, Thuringian Mallow or hemp [23][24][25].…”
Section: Introductionmentioning
confidence: 99%